2007
DOI: 10.1107/s160053680700147x
|View full text |Cite
|
Sign up to set email alerts
|

5-[3-(Dimethylamino)propyl]-10,11-dihydro-5H-dibenz[a,d][7]annulen-5-ol

Abstract: Key indicatorsSingle-crystal X-ray study T = 298 K Mean (C-C) = 0.002 Å R factor = 0.040 wR factor = 0.108 Data-to-parameter ratio = 14.7For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…The bent transition state is an intermediate conformation state of a cycloheptane, between boat and chair, and is characterized in the ideal case by the following contiguous torsion angles as calculated by Bocian et al (1975) and Bocian & Strauss (1977): 75.1, À60.3, À1.8, 1.7, 60.3, À75.1 and 0.0 . Similar conformations of the tricyclic ring were also observed in nortriptyline and amitriptyline hydrochloride (Klein et al, 1991(Klein et al, , 1994 and related compounds (Vijay et al, 2005;Portalone et al, 2007).…”
Section: Commentsupporting
confidence: 64%
“…The bent transition state is an intermediate conformation state of a cycloheptane, between boat and chair, and is characterized in the ideal case by the following contiguous torsion angles as calculated by Bocian et al (1975) and Bocian & Strauss (1977): 75.1, À60.3, À1.8, 1.7, 60.3, À75.1 and 0.0 . Similar conformations of the tricyclic ring were also observed in nortriptyline and amitriptyline hydrochloride (Klein et al, 1991(Klein et al, , 1994 and related compounds (Vijay et al, 2005;Portalone et al, 2007).…”
Section: Commentsupporting
confidence: 64%
“…For structurally related tricyclic antidepressants, see: Cimolai (2009); Commissiong et al (1981); Katz & Dube (1988). For related structures, see: Bindya et al (2007); Fun et al (2011); Portalone et al (2007). For standard bond lengths, see Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…Cyclobenzaprine has been considered structurally related to the first-generation tricyclic antidepressants (Commissiong et al, 1981;Katz & Dube, 1988;Cimolai, 2009). The crystal structures of amitriptylinium picrate (Bindya et al, 2007), 5-[3-(dimethylamino)propyl]-10,11-dihydro-5H-dibenz [a,d][7]annulen-5-ol (Portalone et al, 2007) and cyclobenzaprinium salicylate (Fun et al, 2011) have been reported. In view of the importance of yclobenzaprine, this paper reports the crystal structure of the title compound, C 20 H 22 N + .…”
Section: Data Collectionmentioning
confidence: 99%
“…For related structures, see: Portalone et al (2007); ; Harrison, Bindya et al (2007). For background, see: Cohen et al (1990); Ahmed et al (2002).…”
Section: Related Literaturementioning
confidence: 99%
“…In continuation of our work on the picrate salts of pharmaceutical compounds (Portalone et al, 2007;Harrison, Bindya et al, 2007), we now report the structure of the title compound, (I).…”
Section: Data Collectionmentioning
confidence: 99%